ETIOLOGICAL FACTORS OF CHRONIC GASTRITIS IN CHILDREN - G.V. Volynets ("Paediatrician" Publishers LLC, 2006)
In the article the data on the study of the etiological factors of various types of chronic gastritis in children are presented. Based on revealing of the auto antibodies to parietal gastric cells in 40,0% of children autoimmune gastritis (a type gastritis) is diagnosed. Helicobacterr pylori infection is revealed in 44,8% of children. In 27,6% of children type c gastritis is diagnosed. Autoimmune gastritis in children has been linked to the active phase of chronic epsteinbbarr virus infection. the etiological factors of nonautoimmune gastritis are Helicobacter pylori infection (type b gastritis) and multiple duodenogastric refluxes (type c gastritis).Key words: children, chronic gastritis, etiological factors, autoimmune gastritis, nonautoimmune gastritis, active phase of chronic Epstein-Barr virus infection, Helicobacter pylori infection.